Non-parametric analysis of COVID-19-Driven online shopping behavior in Malaysia / Nurhasniza Idham Abu Hasan ... [et al.] - Abu Hasan, Nurhasniza Idham; Ganggayah, Mogana Darshini; Mat Zin, Siti Hasma Hajar; Abdul Razak, Nur Ain Izzati; Jamal, Nur Faezah (Universiti Teknologi MARA, Perak, 2023)
The COVID-19 pandemic has resulted in a surge in online shopping in Malaysia, which has highlighted the significance of delving into the factors that affect consumers' behavior when making purchases online. A cross-sectional survey was conducted in Malaysia between 3rd December and 27th December 2021. The study aimed to examine the differences in online shopping behavior among Malaysian consumers and used the Mann-Whitney Test and Kruskal Wallis Test for comparison when the normality assumption of the response is not normally distributed. The result demonstrates that there was a significant difference in online shopping behavior between marital status (U=5992.50, p=0.006), gender (U=5992.50, p=0.006), and different age groups (K=21.857, p=<0.001). In conclusion, the study contributes to the understanding of the characteristics of online shopping in Malaysia, including the factors that motivate consumers to shop online and the challenges they face.